2009
DOI: 10.1890/07-1864.1
|View full text |Cite
|
Sign up to set email alerts
|

Including intraspecific variability in functional diversity

Abstract: Linking species and ecosystems often relies on approaches that consider how the traits exhibited by species affect ecosystem processes. One method is to estimate functional diversity (FD) based on the dispersion of species in functional trait space. Individuals within a species also differ, however, and an unresolved challenge is how to include such intraspecific variability in a measure of functional diversity. Our solution is to extend an existing measure to variation among individuals within species. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
167
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 46 publications
4
167
0
13
Order By: Relevance
“…An attribute is the particular value taken by the trait at any place and time (Violle et al 2007). In this case, functional information was site-specific, because we considered the individuals sampled at each site separately, which allowed us to include intraspecific differences among sites (Cianciaruso et al 2009). We measured stem specific density, leaf nitrogen content, and leaf phosphorus content for five individuals per species.…”
Section: Species Richness and Functional Diversity Componentsmentioning
confidence: 99%
“…An attribute is the particular value taken by the trait at any place and time (Violle et al 2007). In this case, functional information was site-specific, because we considered the individuals sampled at each site separately, which allowed us to include intraspecific differences among sites (Cianciaruso et al 2009). We measured stem specific density, leaf nitrogen content, and leaf phosphorus content for five individuals per species.…”
Section: Species Richness and Functional Diversity Componentsmentioning
confidence: 99%
“…The ecological literature about the measurement of functional diversity, which captures how functional trait composition varies among assemblages, has grown during the last decade (i.e., Thompson et al 2005;Barnett and Beisner 2007). Functional diversity can be expressed as the measurement of the branch length of a dendrogram based on similarities between functional traits Gaston 2002, 2009;Cianciaruso et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The diversity index of Shannon-Weaver [32] has been extensively used as a measure of assemblage diversity. All proposed functional diversity measures have assumed that individuals in a given assemblage are equally important, even if they make disproportionate contributions to assemblage function [34]. However, several studies have reported on how variation among individuals of the same species is important for assemblage function [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported on how variation among individuals of the same species is important for assemblage function [35,36]. Up to this point, none of the methods proposed for estimating functional diversity [37] give a clear approach to incorporating information about individuals [34]. Our previous research deduced the diversity index of energy flow based on the Shannon-Wiener index by ecological energetics, as a measure of the functional diversity index, which includes measures that incorporate information about the abundance, age structure, life history, and mortality of each species in a assemblage [18].…”
Section: Discussionmentioning
confidence: 99%